Changes in T-Cell and Monocyte Phenotypes In Vitro by Schistosoma mansoni Antigens in Cutaneous Leishmaniasis Patients - Aline Michelle Barbosa Bafica; Luciana Santos Cardoso; Sérgio Costa Oliveira; Alex Loukas; Alfredo Góes; Ricardo Riccio Oliveira; Edgar M. Carvalho; Maria Ilma Araujo (Journal of Parasitology Research)
High levels of proinflammatory cytokines such as IFN-γ and TNF are associated with tissue lesions in cutaneous leishmaniasis (CL). We previously demonstrated that Schistosoma mansoni antigens downmodulate the in vitro cytokine response in CL. In the current study we evaluated whether S. mansoni antigens alter monocyte and T-lymphocyte phenotypes in leishmaniasis. Peripheral blood mononuclear cells of CL patients were cultured with L. braziliensis antigen in the presence or absence of the S. mansoni antigens rSm29, rSmTSP-2- and PIII. Cells were stained with fluorochrome conjugated antibodies and analyzed by flow cytometry. The addition of rSm29 to the cultures decreased the expression of HLA-DR in nonclassical (CD14+CD16++) monocytes, while the addition of PIII diminished the expression of this molecule in classical (CD14++CD16-) and intermediate (CD14++CD16+) monocytes. The addition of PIII and rSmTSP-2 resulted in downmodulation of CD80 expression in nonclassical and CD86 expression in intermediate monocytes, respectively. These two antigens increased the expression of CTLA-4 in CD4+ T cells and they also expanded the frequency of CD4+CD25highFoxp3+ T cells. Taken together, we show that S. mansoni antigens, mainly rSmTSP-2 and PIII, are able to decrease the activation status of monocytes and also to upregulate the expression of modulatory molecules in T lymphocytes.